The Epidemiology of Venous Thromboembolism in the Community - Heit, John A.; Silverstein, Marc D.; Mohr, David N.; Petterson, Tanya M.; Lohse, Christine M.; O’Fallon, W. Michael; Melton, L. Joseph, III (Thrombosis and Haemostasis, 2001)
The incidence of venous thromboembolism exceeds 1 per 1000; over 200,000 new cases occur in the United States annually. Of these, 30% die within 30 days; one-fifth suffer sudden death due to pulmonary embolism. Despite improved prophylaxis, the incidence of venous thromboembolism has been constant since 1980. Independent risk factors for venous thromboembolism include increasing age, male gender, surgery, trauma, hospital or nursing home confinement, malignancy, neurologic disease with extremity paresis, central venous catheter/ transvenous pacemaker, prior superficial vein thrombosis, and varicose veins; among women, risk factors include pregnancy, oral contraceptives, and hormone replacement therapy. About 30% of surviving cases develop recurrent venous thromboembolism within ten years. Independent predictors for recurrence include increasing age, obesity, malignant neoplasm, and extremity paresis. About 28% of cases develop venous stasis syndrome within 20 years. To reduce venous thromboembolism incidence, improve survival, and prevent recurrence and complications, patients with these characteristics should receive appropriate prophylaxis.
Keywords: Venous thromboembolism; deep vein thrombosis; pulmonary embolism; epidemiology